2014
DOI: 10.31729/jnma.2591
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron and Granisetron for Prevention of Postoperative Nausea and Vomiting following Laparoscopic Cholecystectomy

Abstract: Introduction: Laparoscopic surgeries are known to be associated with a higher incidence of postoperative nausea and vomiting (PONV). Prophylaxis of PONV is usually achieved with a singledose antiemetic drug administered during the surgical procedure. The aim of this study was to compare the antiemetic efficacy of two different 5-hydroxytryptamine-3 (5HT3) receptor antagonists, ondansetron and granisetron when given prophylactically to patients undergoing laparoscopic cholecystectomy.Methods: It was a randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…As a common substitute for traditional open cholecystectomy, LC has been introduced in cholelithiasis management; however, the evidence shows excessive episodes of PONV after LC. [ 18 19 ] Many studies have been conducted to evaluate the efficacy of different antiemetic medications in preventing PONV after LC, with a variable success rate. Such medication may also be problematic in terms of side effects including hypotension, dysphoria, excessive sedation, hallucination and dry mouth.…”
Section: Discussionmentioning
confidence: 99%
“…As a common substitute for traditional open cholecystectomy, LC has been introduced in cholelithiasis management; however, the evidence shows excessive episodes of PONV after LC. [ 18 19 ] Many studies have been conducted to evaluate the efficacy of different antiemetic medications in preventing PONV after LC, with a variable success rate. Such medication may also be problematic in terms of side effects including hypotension, dysphoria, excessive sedation, hallucination and dry mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Gauchan et al evaluated the antiemetic efficacy of Ondansetron and Granisetron in patients undergoing laparoscopic cholecystectomy during the first 24 hours after anaesthesia. They indicated that Granisetron was effectively capable of increasing incidence of PONV as compared to Ondansetron in the first 24 hours [17].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the maximum sample size, the standard deviation in similar studies, alpha coefficient of 5% and power of 80% [16], [17], 120 patients with strabismus surgery were randomly assigned to 3 groups of 40 subjects in the placebo, Ondansetron and Granisetron. Inclusion criteria: 1) Patients undergoing strabismus surgery over the age of 3 years And 2) Class 1 & 2 American Society of Anaesthesiologists' (ASA) classification of Physical Health.…”
Section: Methodsmentioning
confidence: 99%
“…Laparoscopic cholecystectomy is considered now a better substitution for traditional open cholecystectomy in patients suffering from cholecystitis; Unfortunately, Laparoscopic surgeries proved to show excessive episodes of PONV [16] with an incidence of approximately 30% [3,4]. Although many different antiemetic drugs in many studies have been evaluated rather alone or with combination trying to prevent PONV after LC, unsatisfactory results occurred.…”
Section: Discussionmentioning
confidence: 99%